Automated generation of parallel programs for graphics processing units based on algorithm schemes - Doroshenko, А.Yu.; Beketov, O.G.; Ivaniv, R.B.; Iovchev, V.O.; Mironenko, I.O.; Yatsenko, O.A. (Інститут програмних систем НАН України, 2017)
The algebra-algorithmic approach to automated designing and generation of programs for graphics processor units is proposed. The particular feature of our approach consists in using high-level specifications, represented in algebra of algorithms, and applying a method, ensuring the syntactical regularity of algorithms and programs being designed. The approach was implemented in the online toolkit for interactive design of algorithm schemes and generation of programs in target programming languages. The usage of the toolkit is illustrated on development of parallel program for convection-diffusion problem.